Understanding APIs and RESTful APIs Crash Course - Taulien, Kalob (Packt Publishing, 2020)
Discover what APIs and RESTful APIs are and how they work About This Video Get to grips with application program interfaces (APIs) and RESTful APIs and understand how they work Explore the five main request methods - GET, POST, PUT, PATCH, and DELETE Learn the concept of CRUD (create, read, update, and delete) operations and HTTP status codes In Detail This course will help you understand what APIs and RESTful APIs are and how they work. It is designed in such a way that you will learn everything you need without feeling overwhelmed. APIs and RESTful APIs come across as difficult or advanced subjects, but they are just two computers communicating with each other and exchanging commands and data. The videos will take you through several easy-to-remember metaphors so that you can grasp APIs without getting unnerved. Because APIs can be written using different programming languages, this course will not include any coding exercises apart from a JavaScript demo. By the end of this course, you'll have a comprehensive understanding of how APIs work and how computers communicate with each other. You'll also become familiar with RESTful APIs, which make use of the HTTP protocol.